Investigating charm production and fragmentation via azimuthal correlations of prompt D mesons with charged particles in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (The European physical journal. C, Particles and fields, 2022)
Angular correlations of heavy-flavour and charged particles in high-energy proton–proton collisions are sensitive to the production mechanisms of heavy quarks and to their fragmentation as well as hadronisation processes. The measurement of the azimuthal-correlation function of prompt D mesons with charged particles in proton–proton collisions at a centre-of-mass energy of s√=13 TeV with the ALICE detector is reported, considering D0, D+, and D∗+ mesons in the transverse-momentum interval 3<pT<36 GeV/c at midrapidity (|y|<0.5), and charged particles with pT>0.3 GeV/c and pseudorapidity |η|<0.8. This measurement has an improved precision and provides an extended transverse-momentum coverage compared to previous ALICE measurements at lower energies. The study is also performed as a function of the charged-particle multiplicity, showing no modifications of the correlation function with multiplicity within uncertainties. The properties and the transverse-momentum evolution of the near- and away-side correlation peaks are studied and compared with predictions from various Monte Carlo event generators. Among those considered, PYTHIA8 and POWHEG+PYTHIA8 provide the best description of the measured observables. The obtained results can provide guidance on tuning the generators.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ALICE collaboration*: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, M. Kroesen, J.A. Lopez, N.A. Martin, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, B. Volkel, M.A. Völkl, B. Windelband, A. Yuncu [und viele weitere]
Gesehen am 19.10.2022